2005
DOI: 10.1007/s00256-005-0906-y
|View full text |Cite
|
Sign up to set email alerts
|

Rosai-Dorfman disease presenting as multiple soft tissue masses

Abstract: Rosai-Dorfman disease is a rare clinical disorder which may present in many forms. While classically a disease of lymph nodes, soft tissue involvement is fairly common. Soft tissue involvement can occur without any lymphatic or systemic involvement, and may be difficult to diagnose. We describe a patient presenting with multiple soft tissue masses which on biopsy proved to be isolated cutaneous Rosai-Dorfman disease. MR imaging showed two well-defined nonspecific superficial masses that enhanced intensely. Rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 4 publications
1
10
0
Order By: Relevance
“…One report highlights the striking recurrence potential in a case of abdominal wall RDD requiring five reexcisions in 12 years (4) . In a case report similar to the present case, a 40-year-old female patient with two distinct nodules in posterolateral right thigh developed a new nodule in left thigh within one year after surgical resection (8) . Whenever feasible, wide surgical margins should be performed (1,5) as chemotherapy has not proven to be useful (5,9) .…”
Section: Case Report and Discussionsupporting
confidence: 79%
“…One report highlights the striking recurrence potential in a case of abdominal wall RDD requiring five reexcisions in 12 years (4) . In a case report similar to the present case, a 40-year-old female patient with two distinct nodules in posterolateral right thigh developed a new nodule in left thigh within one year after surgical resection (8) . Whenever feasible, wide surgical margins should be performed (1,5) as chemotherapy has not proven to be useful (5,9) .…”
Section: Case Report and Discussionsupporting
confidence: 79%
“…5,11 Multifocal STRDD is extremely uncommon but recurs more frequently than a solitary lesion. 11,12 The rate of recurrence of STRDD after excision has been reported to range from 21.4-54%. 5,11 Immunohistochemistry is key to differentiating soft tissue lesions in order to determine the correct diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported female predominance for STRDD over a wide range of ages with variable-sized masses [ 5 , 6 ]. A higher recurrence rate has been suggested for STRDD with multicentric lesions compared to solitary lesions [ 7 ]. The present case was a solitary lesion at diagnosis, and the patient is receiving regular follow-up.…”
Section: Discussionmentioning
confidence: 99%